SOCIO-ECONOMIC PARAMETERS OF DAIRY OWNERS OF TRIBAL AND NON TRIBAL AREAS IN UDAIPUR DISTRICT (Indian Journal of Animal Production and Management, 2014)
Present study was conducted in Udaipur district of Rajasthan, four tehsils were selected for sampling under rural areas which included tribal and nontribal villages. Sixteen villages (eight tribal and eight non-tribal) were randomly selected from each tehsils. Thirty dairy farmer families were selected in each village. For selection of tehsil and village, census report and district hand book was consulted. An interview schedule was developed and pretested to collect relevant information on the socio economic aspects of dairy cattle and buffalo’s management. The literacy and educational status of family head was higher in non tribal than tribal areas. The proportion of SC and ST farmers were higher in tribal area, while general casts in non tribal areas. All the nontribal and tribal farmers followed mixed framing. The total income per family per year was higher (Rs 20,000.00) in nontribal area as compared to tribal area (Rs. 10,000.00). The income from dairy component was considerably higher in nontribal area (50 percent) than tribal area. The average land holding per family was 140.27 and 94.53 hectors in non tribal and tribal areas. Most of tribal farmers have (62.25 percent) and in nontribal areas (54.16 percent). Maize is main kharif crop and wheat’s rabi crop, while lucerne are main green fodder crops among the other fodder crops in the tribal and non tribal areas of Udaipur district of Rajasthan.
Keywords: Tribal; non- tribal; Socio-economic parameter; Dairy owner